Les réseaux d’alimentation en eau des pentes de la Croix-Rousse et de la presqu’île de Lyon - Jules Ramona (Gallia)
Until recently, work on the ancient hydraulics of Lyon had essentially focused on the upper city. Although the existence of a pressurised water system in the lower city was suspected, no synthesis had been conducted on the subject. Drawing on a comprehensive collection of data relating to water-related structures (wells, pipes, basins and fountains), the objective of the article is to review the state of knowledge about the modes of water supply on the slopes of the Croix-Rousse and the Presqu’île. In spite of the restrictive conditions of human settlement on the alluvial terrace, the study area offers significant and diverse aquifer potential which has been exploited since the earliest days of occupation.The wells, connected to the Croix-Rousse catchment galleries or to the ground-water tables of the Presqu’île, were widely used throughout the Ancient period. They are quite similar, generally circular and lined with local stones, with a diameter of between 0.60 and 1.20 m. Sometimes their identification is lacking. They can therefore be interpreted as drainage structures, such as sumps, generally associated with artisanal activities. Probably an addition to rainwater resources, they seem to be non-uniformly distributed over the study area.A little later, perhaps from the end of the 1st century AD, the presence of a public pressurised water supply system suggests that the lower city was no longer just a sanitised alluvial wasteland, punctuated by a few buildings constructed of light materials, but a planned and densely populated permanent urban space. Sections of pipe are thus observed in situ, outside the large domus on the slopes of the Croix-Rousse (ZAC Saint-Vincent) and in the north and centre of the Presqu’île (Îlot Vieille Monnaie, Hôtel-Dieu), or in the direct vicinity of the presumed location of a public fountain (Place d’Albon). As is often the case, lead pipes are missing. Having been systematically removed and reused, they can only be found in a secondary context. However, the discovery of a flanged lead pipe in situ on the Hôtel-Dieu site is an exception. It is also demonstrates for the first time in Lyon the existence of a hybrid lead-wood adduction system.The frequent presence of metal sockets under the outdoor spaces prompts us to consider the widespread use of this type of water supply in a public context. Similarly, the two long clay pipes recently uncovered on the Hôtel-Dieu and Saint-Antoine parking sites are probably linked with an outdoor space. They may have been used, during the same periods, in addition to wooden pipes. However, the nature of their relationship (parallel or hierarchical?) needs to be clarified. Dedicated to thermal activities or to the supply of fountains, the presence of a forced water system suggests the existence of an imposing and complex public supply system.Lastly, the analysis of the hydraulic installations of use can be used to attempt a classification according to supply modes. The study sector thus includes a large number of ponds, probably fed by rainwater (mainly handicraft ponds and outdoor ornamental ponds). There are few devices that we can be sure were supplied with forced clean water. The thermal complexes of the old Monnaie block and of ZAC Saint-Vincent, as well as the public fountain on Place d’Albon are part of it.Ultimately, the study tells us that all the resources available on the zone were directly and efficiently exploited, whether in public, housing or artisanal contexts. Technically difficult to implement, the forced clean water supply and its public character raise questions. While the existence of this system is clearly attested on the slopes of the Croix-Rousse at least from the Claudian period, and from the Flavian period in the north and centre of the Presqu’île, the origin of its water sources, the technical conditions of its operation and the limits of its geographical scope remain speculative. We believe that the source of the network’s supply could be the catchment galleries. Hence, the water would arrive via a main supply network and would then be distributed to the various districts of the lower town by means of distribution tanks, supplemented by a secondary system made up of smaller diameter pipes. Deployed in the lower part of the city, the network might have been lined with secondary water towers such as those observed in Pompeii. Moreover, the absence of evidence of forced water pipes in the southern part of the Peninsula could be attributable to a technical geographical limit on the distribution of water under pressure. In fact, this sector is characterised by a large number of wells. The filling of one of these wells delivered a rare surviving example of a wooden hydraulic pump. In the absence of a pressurised water system, the hypothesis of a complementary water supply for this sector is seems plausible.